2020
DOI: 10.1186/s13011-020-00260-y
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines in the oral fluid of Spanish drivers

Abstract: Background: Driving under the influence of alcohol, illicit drugs and certain medicines is not allowed worldwide. Roadside drug testing is considered an important tool for determining such behavior. In Spain, mandatory roadside oral fluid drug testing is carried out regularly. The aim of this study was to determine the prevalence of benzodiazepines and benzodiazepines in combination with other drugs in drivers, examine benzodiazepine concentrations in drivers, and analyze the association of these factors with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The increased accident risk when driving with the presence of other drugs is well known. This finding is consistent with polysubstance use observed when assessing confirmed tests for opioids and cannabis in the same period in Spain [ 13 , 14 ] and worldwide [ 2 , 4 , 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The increased accident risk when driving with the presence of other drugs is well known. This finding is consistent with polysubstance use observed when assessing confirmed tests for opioids and cannabis in the same period in Spain [ 13 , 14 ] and worldwide [ 2 , 4 , 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…As previously performed [ 5 , 13 , 14 ], this study assessed Spanish National administrative data on laboratory-confirmed drug-positive results obtained from the Spanish National Traffic Agency records corresponding to licensed drivers who underwent drug confirmation analyses between 1 January 2011, and 31 December 2016. Hypothesis, analysis and reporting follow the REporting of studies Conducted using Observational Routinely collected health Data (RECORD) guidelines [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations